On a new one-step method for numerical solution of initial-value problems in ordinary differential equations - Kama, P.; Ibijola, E.A. (International journal of computer mathematics, 2001)
In this paper, we propose a numerical algorithm which is based on the representation of the theoretical solution by a perturbation of a polynomial interpolating function with an exponential function. The numerical algorithm is stable, consistent and convergent. Some numerical results were obtained to illustrate the accuracy of the algorithm.